Advances in molecular toxicology Volume 7 - Fishbein, James C.; Heilman, Jacqueline M. (Amsterdam, Netherlands ; Oxford, England : Elsevier, 2013)
Advances in Molecular Toxicology features the latest advances in the subspecialties of the broad area of molecular toxicology. This series details the study of the molecular basis of toxicology by which a vast array of agents encountered in the human environment and produced by the human body manifest themselves as toxins. The book is not strictly limited to documenting these examples, but also covers the complex web of chemical and biological events that give rise to toxin-induced symptoms and disease. The new technologies that are being harnessed to analyze and understand these events will also be reviewed by leading workers in the field.
6.2. Phenylenediamine arylamine xenobiotics7. Arylamine Drugs and Blood Dyscrasias; 7.1. Procainamide; 7.2. Aminoglutethimide; 7.3. Aminopyrine; 8. Diverting Toxic Arylamine Free Radical Generation to Detoxification: Importance of Free Radical Targets; 9. Mixtures Toxicology-Application to Arylamine Free Radicals; 10. Protein Radicals and Toxicity-Future Prospects; 11. Closing Remarks; References; Chapter Three: Genotoxicity of Polycyclic Aromatic Hydrocarbon Metabolites: Radical Cations and Ketones; 1. Introduction; 2. Exposure to PAHs; 3. Exposure Risks of PAH; 4. DNA Damage by PAH
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Included bibliographical references at the end of each chapters and index.
Mode of access: Internet
Keywords: Molecular biology; Toxicology; Molecular biology; Toxicology; Electronic books